Long term survival and disease burden from out-of-hospital cardiac arrest in Singapore: a population-based cohort studyResearch in context - Andrew Fu Wah Ho; Mervyn Jun Rui Lim; Arul Earnest; Audrey Blewer; Nicholas Graves; Jun Wei Yeo; Pin Pin Pek; Ling Tiah; Marcus Eng Hock Ong; Michael Y.C. Chia; Yih Yng Ng; Benjamin S.H. Leong; et al. (The Lancet Regional Health. Western Pacific, 2023)
Summary: Background: Understanding the long-term outcomes and disability-adjusted life years (DALY) after out-of-hospital cardiac arrest (OHCA) is important to understand the overall health and disease burden of OHCA respectively, but data in Asia remains limited. We aimed to quantify long-term survival and the annual disease burden of OHCA within a national multi-ethnic Asian cohort. Methods: We conducted an open cohort study linking the Singapore Pan-Asian Resuscitation Outcomes Study (PAROS) and the Singapore Registry of Births and Deaths from 2010 to 2019. We performed Cox regression, constructed Kaplan–Meier curves, and calculated DALYs and standardised mortality ratios (SMR) for each year of follow-up. Results: We analysed 802 cases. The mean age was 56.0 (SD 17.8). Most were male (631 cases, 78,7%) and of Chinese ethnicity (552 cases, 68.8%). At one year, the SMR was 14.9 (95% CI:12.5–17.8), decreasing to 1.2 (95% CI:0.7–1.8) at three years, and 0.4 (95% CI:0.2–0.8) at five years. Age at arrest (HR:1.03, 95% CI:1.02–1.04, p < 0.001), shockable presenting rhythm (HR:0.75, 95% CI:0.52–0.93, p = 0.015) and CPC category (HR:4.62, 95% CI:3.17–6.75, p < 0.001) were independently associated with mortality. Annual DALYs due to OHCA varied from 304.1 in 2010 to 849.7 in 2015, then 547.1 in 2018. Mean DALYs decreased from 12.162 in 2010 to 3.599 in 2018. Conclusions: OHCA survivors had an increased mortality rate for the first three years which subsequently normalised compared to that of the general population. Annual OHCA disease burden in DALY trended downwards from 2010 to 2018. Improved surveillance and OHCA treatment strategies may improve long-term survivorship and decrease its global burden. Funding: National Medical Research Council, Singapore, under the Clinician Scientist Award (NMRC/CSA-SI/0014/2017) and the Singapore Translational Research Investigator Award (MOH-000982-01).